2019
DOI: 10.17507/jltr.1001.04
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Stay-abroad Experiences, Frequency Effects, and Context Use in L2 Idiom Comprehension

Abstract: This article explores to what extent a stay-abroad experience of L2 learners leads to more productive use of contextual clues and better benefits from frequency effects in L2 idiom comprehension. To this end, seventy-two learners of German (L1 French) were presented with a test on idiom comprehension that contained items both with and without a context and differing degrees of frequency. Furthermore, the participants completed a questionnaire on their stay-abroad experience (length of stay, country, etc.) as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…De Cock and Suñer (2018) found that a stay abroad does influence the comprehension of metaphors associated with sexual taboo, highlighting the role of cultural exposure in understanding sensitive linguistic nuances. However, this effect was not observed in the comprehension of expressions from other (more general) topic domains, as reported by Suñer (2019), which suggests that learners mobilize different knowledge resources and deploy qualitatively different strategies for processing taboo language when compared to more formal registers.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…De Cock and Suñer (2018) found that a stay abroad does influence the comprehension of metaphors associated with sexual taboo, highlighting the role of cultural exposure in understanding sensitive linguistic nuances. However, this effect was not observed in the comprehension of expressions from other (more general) topic domains, as reported by Suñer (2019), which suggests that learners mobilize different knowledge resources and deploy qualitatively different strategies for processing taboo language when compared to more formal registers.…”
Section: Introductionmentioning
confidence: 66%
“…Moreover, we did not find a significant effect of students' proficiency in Spanish or the experience gained through a stay abroad on the responses (Hypothesis 2), even though both variables did increase the proportion of correct results. The lack of significance might push further a reflection that was brought up in the introduction: in previous studies, a stay abroad had significant effects on the interpretation of sexual metaphors (De Cock and Suñer 2018), but not on other, more formal registers (Suñer 2019), which was interpreted as a difference in the knowledge resources and strategies that students mobilize for processing taboo language as compared to more formal registers. Here, although we found that the stay-abroad experience helps, it does not reach significance when interpreting taboo language.…”
Section: Discussionmentioning
confidence: 95%
“…For example, Suñer (2018) found out that L2 idiom comprehension was positively correlated with the general proficiency level of learners, rather than with stay‐abroad experience (see also Galantomos, 2018). A follow‐up study by Suñer (2019) showed that participants with a stay‐abroad experience neither outperformed those without such an experience nor benefited from frequency effects and the presence of context. However, it must be noted that both studies did not include any taboo expressions, but metaphorical expressions from more general topic domains.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it seems of relatively less direct impact on L2 idiom learning (see e.g., Suñer, 2019 with a plea for increasing enhanced input and explicit knowledge of idioms for L2 learners even in the stay-abroad learning context). First, research evidence shows that item frequency based on the British National Corpus (BNC) and Collins Cobuild Idioms Dictionary (2002) does not seem to predict whether an L2 learner (and also a L1 speaker) will know the meaning of an idiom (Karlsson, 2013).…”
Section: Other Factors and Considerations For This Studymentioning
confidence: 99%